Spontaneous regression of pancreatic cancer with liver metastases. Issue 5 (31st May 2019) - Saade Lemus, Patricia; Anderson, Kevin; Smith, Martin; Bullock, Andrea
Abstract : Spontaneous cancer regression is a rare event, scarcely reported among gastrointestinal malignancies. Pancreatic adenocarcinoma regression has been documented in five previous cases, none of which included liver metastases, and the mechanism by which this occurs is not known. A 56-year-old woman with history of discoid lupus, homocysteinemia and peripheral vascular disease was diagnosed with stage IV pancreatic ductal adenocarcinoma (PDA) metastatic to the liver. She received palliative chemotherapy with 5-fluorouracil, leucovorin, irinotecan and oxaliplatin (FOLFIRINOX) for 6 months, complicated by mucositis, diarrhoea, vomiting and two Clostridium difficile colitis episodes. Cancer initially responded to chemotherapy. However, due to substantial toxicities, she decided to discontinue cytotoxic chemotherapy and focus on palliation alone. Thereafter, CT and carbohydrate antigen (CA) 19-9 showed further response and ultimately complete cancer regression that has persisted for 33 months after cessation of chemotherapy. This is the first report in the English literature showing spontaneous regression of a PDA with liver metastases. Two possible mechanisms are proposed: antitumoral autoimmunity and tumour hypoxia related to vascular disease.